2022
DOI: 10.3389/fnagi.2022.868158
|View full text |Cite
|
Sign up to set email alerts
|

Potential Markers of Neurocognitive Disorders After Cardiac Surgery: A Bibliometric and Visual Analysis

Abstract: BackgroundIdentifying useful markers is essential for diagnosis and prevention of perioperative neurocognitive disorders (PNDs). Here, we attempt to understand the research basis and status, potential hotspots and trends of predictive markers associated with PNDs after cardiac surgery via bibliometric analysis.MethodsA total of 4,609 original research articles and reviews that cited 290 articles between 2001 and 2021 were obtained from the Web of Science Core Collection (WoSCC) as the data source. We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Consistent with cognitive disorders like AD and MCI, and in addition to memory deficits, impairment in other cognitive domains is present in DNR. Many studies used neuropsychological tests to demonstrate visual cognitive dysfunction in DNR patients (Lage et al, 2021;Ji and Li, 2022;Zhao et al, 2022). We also found that the DNR patients showed poor performance postoperatively in visual attention, visual memory, visual-spatial scanning, and visual search speed assessed by DSST and TMT-A.…”
Section: Discussionmentioning
confidence: 59%
“…Consistent with cognitive disorders like AD and MCI, and in addition to memory deficits, impairment in other cognitive domains is present in DNR. Many studies used neuropsychological tests to demonstrate visual cognitive dysfunction in DNR patients (Lage et al, 2021;Ji and Li, 2022;Zhao et al, 2022). We also found that the DNR patients showed poor performance postoperatively in visual attention, visual memory, visual-spatial scanning, and visual search speed assessed by DSST and TMT-A.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, increased levels of cerebral kynurenic acid have been detected in the aged brain and in several major neurological and psychiatric diseases [ 85 ]. Kynurenic acid has been also suggested to be related to cognitive impairments [ 86 ], which have been frequently discussed as possible markers of perioperative neurocognitive disorders [ 87 ]. A lower level of kynurenic acid has been associated with worse cognitive functioning in a bipolar depression group [ 88 ] ( Figure 2 ).…”
Section: Kynurenine Metabolites Involved In Brain Memory System and I...mentioning
confidence: 99%
“…The succinct summary of research contents using keywords allows for an analysis of high-frequency keywords, providing insight into the main research content and hot topics within a particular field. [86][87][88] Figure 9 depicts the cooccurrence relationship and average appearance time of keywords appearing no less than 15 times. It can be observed that keywords such as biomechanics, lumbar spine, and IVD appear earlier due to the focus of the study, while keywords such as finite element analysis (FEA), low back pain, and IVD degeneration occur frequently in recent years.…”
Section: Analysis Of Abstractmentioning
confidence: 99%